DECISION SUPPORT SYSTEM DETERMINES THE PURCHASE OF HOUSE RIGHT USING ANALYTICAL HIERARCHY PROCESS (AHP) AND BORDA METHODS - Didit Herdiawan Ashaf; Sutikno Wahyu Hidayat; Ahmadi Ahmadi (JOURNAL ASRO, 2019)
Increasing population growth also contributes to the increasing need for homes or dwellings as basic human needs. Many ways people do to meet these needs, among others, by buying from someone else, building it yourself or by buying a house in a housing developer. Houses besides being a basic human need, it is also used as an indicator of one's success and as an asset for business development and an increase in the economic value of the owner. Prospective home buyers certainly have criteria that are considered in choosing a house. Many of the existing criteria are often followed by the availability of more than one choice of the house to be able to meet these criteria. Therefore, the writer tries to try to make a Decision Support System in a Home Purchase that will later help prospective home buyers in deciding which house to buy. The decision-making method used in this system is an analytical hierarchy process (AHP) as a form of decision-making model that is suitable for multi-criteria and multi-alternative problems with the main input being human perception. Combined with the Borda method which is one method of group decision making that can combine the results of perceptual analysis (the results of AHP analysis) from several decision makers. it is necessary to have a group decision-making technique (group decision support system). So that the resulting home purchase decision can be accepted by all decision makers (family). From the results of the calculation and voting process, House X was chosen with 9 votes. Keywords: Home Purchase, Analytical Hierarchy Process, Borda